Le sens de l’écriture chez Michel de Certeau - Pierre Antoine Fabre (Les Dossiers du GRIHL)
Michel de Certeau is often considered as writing at the limits of poetry. How can we understand this way of writing which is often considered out of any strong necessity? Such is the question addressed in this paper. Starting with a detour through the emergence of the metaphor in a text of François de Sales, and through the unveiling of his theological implications, I try to tackle the metaphorical practice at stake in scholarly writing of Certeau, dually based on a founding reference and in a constitutive gap towards Scripture. This essay also attempts to locate this singular work within the more general context of the status and meaning of the act of writing in human sciences, particularly in semiology.